Pengaruh Model Pembelajaran Card Sort Terhadap Hasil Belajar PPKn Siswa Sekolah Dasar - Fitriyani Yusuf; Rien Anitra; Rini Setyowati (Pedagogik Journal of Islamic Elementary School, 2022)
The purpose of this study is to determine the effect of using the card sort learning model on the learning outcomes of fourth-grade civics on the subject of ethnic and religious diversity in my country. This research was conducted at the State Elementary School 03 Rambayan, Sambas Regency. The type of research used is a quantitative experiment with a quasi-experimental design method. The research design used is a nonequivalent control group design. The population of this study was all fourth-grade students of the State Elementary School 03 Rambayan, Sambas Regency, with the sampling technique being in the form of a saturated sample (total sampling). The study was conducted in two classes, namely the experimental class using the card sort learning model with 30 students and the control class using the direct learning model with 30 students. The data collection technique in this study used multiple-choice objective test techniques. The results of the research can be concluded that: (1) There are differences in the learning outcomes of Civics Education aspects of material knowledge of ethnic and religious diversity in my country on the card sort learning model compared to the direct learning model in class IV the State Elementary School 03 Rambayan, Sambas Regency, which was analyzed using the t-test with t_count> t_table is 6.139>2.00172; (2) There is an increase in PPKn learning outcomes in terms of material knowledge of ethnic and religious diversity in my country on the card sort learning model compared to the direct learning model in class IV the State Elementary School 03 Rambayan, Sambas Regency by 0.54 (medium criteria); (3) The card sort learning model has a high influence on student Civic Education learning outcomes on the subject of ethnic and religious diversity in my country, grade IV, which is 2.41 (high criteria).